Female Somalian patient with heart failure diagnosed with tropical endomycocardial fibrosis: A Case Report. Issue 2 (April 2019) - Kalkan, Alev; Dabir, Darius; Klingel, Karin; Nickenig, Georg; Werner, Nikos; Becher, Ulrich M
No abstract available